1973
DOI: 10.1002/polc.5070430108
|View full text |Cite
|
Sign up to set email alerts
|

The thermal breakdown mechanism of polybenzoxazoles and polybenzothiazoles

Abstract: Polybenzoxazoles, when heated up to 660°C in vacuum, lose most of their oxygen as carbon monoxide and carbon dioxide and possibly form Schiff base‐type structures. The carbon required for the formation of carbon monoxide is predominantly supplied by the benzene rings. About one out of every six CN linkages is eliminated as hydrogen cyanide, and some free nitrogen from this group is reduced to ammonia. The elimination of about 1 hydrogen atom per polymer unit (in the form of free hydrogen, hydrogen cyanide, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was concluded that the main route was that of the cleavage of aromatic C-CO of the amide linkages, which led to the formation of carbodiimide bonds [142]. Temperature dependent mechanisms involving iminol tautomerization, condensation of iminols, hydrolysis and decarboxylation was also reported [143].…”
Section: Synthesismentioning
confidence: 99%
“…It was concluded that the main route was that of the cleavage of aromatic C-CO of the amide linkages, which led to the formation of carbodiimide bonds [142]. Temperature dependent mechanisms involving iminol tautomerization, condensation of iminols, hydrolysis and decarboxylation was also reported [143].…”
Section: Synthesismentioning
confidence: 99%
“…However, oxazole decomposition with acetylene formation is estimated to be more energy consuming than decomposition (4) and is, therefore, not considered. Maleimide decomposition with acetylene formation is close in ED to decompositions ( 5 ) and (6). However, in aromatic polyimides the maleimide ring is condensed with a benzene ring, and maleimide decomposition with formation of acetylene corresponds to decomposition of the condensed system with formation of the unstable biradical-like didehydrobenzene.…”
Section: Dissociation Mechanisms Of Oxazole and Maleimidementioning
confidence: 65%
“…As in the case of oxazole, symmetry properties do not favor concerted mechanisms of maleimide decompositions ( 5 ) and (6). For this reason only two-step mechanisms were considered.…”
Section: Maleimide Decompositionmentioning
confidence: 99%